Simple and rapid direct cloning and heterologous expression of natural product biosynthetic gene cluster in Bacillus subtilis via Red/ET recombineering - Liu, Qingshu (Sci Rep, 2016)
Heterologous expression of biosynthetic pathways is an important way to research and discover microbial natural products. Bacillus subtilis is a suitable host for the heterologous production of natural products from bacilli and related Firmicutes. Existing technologies for heterologous expression of large biosynthetic gene clusters in B. subtilis are complicated. Herein, we present a simple and rapid strategy for direct cloning based heterologous expression of biosynthetic pathways in B. subtilis via Red/ET recombineering, using a 5.2 kb specific direct cloning vector carrying homologous sequences to the amyE gene in B. subtilis and CcdB counterselection marker. Using a two-step procedure, two large biosynthetic pathways for edeine (48.3 kb) and bacillomycin (37.2 kb) from Brevibacillus brevis X23 and B. amyloliquefaciens FZB42, respectively, were directly cloned and subsequently integrated into the chromosome of B. subtilis within one week. The gene cluster for bacillomycin was successfully expressed in the heterologous host, although edeine production was not detectable. Compared with similar technologies, this method offers a simpler and more feasible system for the discovery of natural products from bacilli and related genera.